Nilai-Nilai Kearifan Lokal Dalam Pendidikan Multikultural di SDN Tambakromo 01 - Luthfiana Azizatul ‘Uula; Sri Surachmi; Sri Utaminingsih (Peneliti.net, 2022)
Geographical factors that exist in Indonesia with a variety of local wisdom wealth in it are owned by the Indonesian people. Both of these things have message and moral values ​​that were passed down by their ancestors. Culture or local wisdom in each region makes Indonesia a country that has a high diversity. Having a diverse and diverse culture in Indonesia is called multiculturalism. The concept of multiculturalism is a concept of national and state life, as well as an acknowledgment of the existence of democratic values. In order for the concept of multiculturalism to develop and be recognized as a unifier between cultures, it is necessary to teach and train the next generation of the nation through the educational process in the education unit. The purpose of this study is to provide deeper knowledge and insight regarding the form of application of local wisdom values ​​in Pati in multicultural education at SDN Tambakromo 01. The research method used in this study is a qualitative approach with a pheomenological model. By applying the values ​​of local wisdom that exist in Pati in multicultural education in elementary schools, it can create tolerance among students of various cultures, and foster mutual respect, and get used to behaving by upholding the culture of courtesy in everyday life.